English for Students in Faculty of Economic Studies IAIN Curup - Anita, Anita (Linguists : Journal of Linguistics and Language Teaching, 2019)
Since the issue upon ASEAN as a single market and production base becomes tangible, people in business field are encouraged to compete with others. According to this, the working competition will be very tight. In finding a job, they will not only compete with people in their countries but also in South East Asia. Therefore, a good communicative skill in English is needed to broad their networking and knowledge. The issue does not only affect businessmen, but also other people from other fields regarding business, for instance, education. In this case, students from economic major should prepare themselves to face the competition. Thus, the present paper aims to discuss a new curriculum design for students in faculty of economic studies in IAIN Curup through conducting R and D. The writers believe that students are better taught using PPP method which is one of the methods in Audio-lingual approach. This approach derives from behaviorist theory in which students are deductively taught English since they have low level of English proficiency. The design also generates a module which is especially designed for students in faculty of economic studies in IAIN Curup. The curriculum are in the form of syllabus employs PPP method which uses communicative function as the orientation.Keywords: R and D, Audio-lingual, behaviorist, PPP, and ESP